Cyber terorizam - Bezdrob, Enes (Kriminalističke teme, 2019)
Inspiracija za rad i problem (i) koji se radom oslovljava (ju): U prvom dijelu radu se problematizira način kreiranja teoretskog okvira za analiziranje fenomena „cyber terorizma“. U drugom dijelu rada se analizira fenomen „virtualnog genija“. Ova pojava je specifičan produkt posredne komunikacije dostupne na društvenim mrežama. U trećem dijelu rada autor raspravlja o otpornosti društvenih grupa na indoktrinaciju koja se odvija u cyber prostoru. Ciljevi rada (naučni i/ili društveni): Upravo je cyber prostor, svojom specifičnošću dozvolio izranjanje genijalaca koji na izgled imaju puno veće znanje od osoba sa kojima dolazimo u dodir u direktnoj svakodnevnoj komunikaciji. U ovom radu se raspravlja i o vrstama poruka koje se nastoje odaslati i steći naklonost ili, kao forma specijalnog rata, izazvati strah u određenoj društvenoj zajednici. Metodologija/Dizajn: U radu je korištena analiza sadržaja relevantne literature. Ograničenja istraživanja/rada: Rad je pregledni naučni. Rezultati/Nalazi: Gotovo da ne postoji strukturirana društvena zajednica koja nije na neki način upoznata sa materijalnim i intelektualnim resursima i potencijalima njenih članova, sa prednostima i nedostacima socijalizacije unutar grupe. Upravo ovdje je šansa za preventivno djelovanje i sprečavanje eventualnih cyber podstrekača da pronađu stvarne izvršioce terorističkih akata. Generalni zaključak: Ključno je naglasiti da postoji potreba razumijevanja onih koji regrutiraju izvršioce terorističkih akata, njihovih motiva, metoda djelovanja i prepoznavanja potencijalnih istomišljenika. Poseban naglasak se stavlja na profil podstrekača koji iskorištava slabosti eventualnog izvršioca predstavljajući se kao njegov istomišljenik i ohrabruje odnosnog na poduzimanje nasilnih aktivnosti na osnovu činjenica i po-java koje sam izvršilac smatra da treba ispraviti u njegovom okruženju. Opravdanost istraživanja/rada: Poseban problem nastaje pri pokušaju da se ovaj fenomen promatra izdvojeno od ostalih negativnih oblika društvenosti. Naravno, autor prepoznaje specifičan, tehnološki, uvjet koji bi, na prvu, ukazivao da se radi o posebnom obliku terorizma. Međutim, evolucija društvene dinamike ne mijenja posljedicu djelovanja onih koji se bave terorizmom. Važan aspekt zamjene teza je i u činjenici da su u propagiranje ove nove „naučne discipline“ snažno uključeni i mediji ne praveći razliku između nauke i naučne fantastike koju „učenjaci“ željni slave namjerno izostav-ljaju. Cyber Terrorism Reason for writing and research problem (s): In the first part of the paper, the way theoretical frame for the analysis of the “cyber terrorism” phenomenon was created, is problematized. The second part of the paper analyses the “virtual genius” phenomenon. This appearance is a specific product of indirect communication available on social networks. In the third part of the paper the author discusses the resilience of social groups to indoctrination that occurs in cyber space. Aims of the paper (scientific and/or social): It is cyber space, with its specificity, that allows the emerging of geniuses who, at first glance, have a larger knowledge then people; we come in contact in everyday communications. This part also deals with the types of messages that are conveyed in order to gain favor or, as a form of special war, cause fear in a specific social community. Methodology/Design: Paper is a review paper. Research/Paper limitation: This paper employed content analysis of relevant literature. Results/Findings: A structured social community, not familiar with the material and intellectual resources and potential of its members, together with the advantages and disadvantages of socialization inside of the group, almost does not exist. Right here is the chance for prevention and the stopping of potential cyber persuaders to find actual executors of terrorist acts. General Conclusion: It is crucial to emphasize that a need exists to understand those who recruit the executors of terrorist acts, their motives, methods, and the way they recognize potential supporters. A special emphasis is put to the profile of the persuader who uses the weaknesses of potential executors appearing as a like-minded individual and encouraging him to conduct violent activities based on the facts and appearances that the executor himself believes need fixing in his surroundings. Research/Paper Validity: A particular problem occurs when trying to view this phenomenon separately from other negative social forms. Of course, the author recognizes a specific, technological, environment that would, at first, point out that it is a special form of terrorism. However, the evolution of social dynamics does not change the con-sequence of the activities those who engaged in terrorism. An important aspect of this scientific error is in the fact that media are strongly involved in the propagation of this new “scientific discipline” without making a difference between science and science fiction which is deliberately left out by fame craving “scholars”.